IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI SUMBER DAYA ALAM HAYATI DAN NON-HAYATI DI KELAS V SD NEGERI MALANGAN - Vinda Ayu Pratama Ayu; Azamul Fadly Noor Muhammad (STKIP Subang, 2026)
This study aims to describe the implementation of interactive learning media on biotic and abiotic natural resources material in fifth grade elementary school. This research used a qualitative descriptive approach conducted at SD Negeri Malangan with the research subjects consisting of the fifth grade teacher and 15 students. Data collection techniques were carried out through observation, interviews, and documentation. Observation was conducted on April 30, 2026, while interviews were conducted on May 6, 2026, with the classroom teacher, principal, and students. The results showed that the use of interactive learning media such as interactive PowerPoint, group-based student worksheets, and evaluation using Wordwall was able to increase students’ attention, motivation, and participation during the learning process. Students became more active in asking questions, discussing, and understanding the material on biotic and abiotic natural resources because the learning process was related to daily life. Therefore, the implementation of interactive learning media can be an effective alternative in improving the quality of science and social studies learning in elementary schools.